Polaritons em cristais fotônicos intercalados com grafeno - Soares, Pablo José Lima (2019)
We presented an electromagnetic wave propagation in periodic and quasiperiodic (Fibonacci type) multilayer structures, intercalated by a graphene layer, using a theoretical model based on a transfer matrix treatment to simplify the algebra which can be otherwise quite heavy. The multilayer structure is composed by two materials A and B with positive and negative refraction indexes in the terahertz (THz) region. Medium A is a semiconductor (silicon carbide - SiC), with a plasmon-phonon dielectric function and a constant magnetic permeability. Medium B is a metamaterial (lithium tantalate - LiT aO3) with a plasmon-polariton type dielectric function and a Drude type magnetic permeability. We discussed the photonic band gap spectra for both the ideal cases, where the refractive index dependent on the frequency of one of the materials can be considered constant in the the frequency range investigated, as well as the more realistic case, taking into account frequency-dependent refraction index for both materials. The so-called zero-gap region of the mean refractive index η of the photonic structure is also investigated. We also presented a quantitative analysis of the results, pointing out the distribution of the allowed photonic bandwidths for high generations, which gives a good insight about their localization and power laws.